Efficacy of CBT, intensified tDCS and their combination for reducing clinical symptoms and improving quality of life in social anxiety disorder with comorbid depression: a randomized controlled trial - Parinaz Sadat Amiri Sararudi; Mohammad Sadegh Khakpour; Morteza Kazemi; Seyedeh Elnaz Mousavi; Michael A. Nitsche; Mohammad Ali Salehinejad; Mohsen Dadashi (BMC Psychiatry)
Abstract Background/aim Social anxiety disorder (SAD) is a common and disabling psychiatric disorder. It is generally treated with medication and psychotherapy such as cognitive-behavioral therapy (CBT). Due to the involvement of cortical and subcortical areas in the pathophysiology of SAD, non-invasive brain stimulation techniques such as transcranial Direct Current Stimulation (tDCS) are potential adjunctive treatment options for SAD. This study aims to assess comparable efficacy of CBT, intensified tDCS, and combined CBT/tDCS on clinical symptoms and quality of life of patients with SAD and comorbid depression. Methods In this randomized controlled trial, 37 adults with SAD and comorbid depressive disorder were assigned into three groups: (1) CBT + active tDCS (n = 13), (2) active tDCS alone (n = 12), and (3) CBT + sham tDCS (n = 12). SAD symptoms, depressive states, quality of life and trait worry were assessed with the Liebowitz Social Anxiety Scale, Beck’s Depression Inventory, QOL questionnaire (WHOQOL-BREF), and the Penn State Worry Questionnaire respectively. The active tDCS was an intensified stimulation protocol (20 min, twice-daily sessions with 20 min intervals, 5 consecutive days) and was applied over the left dorsolateral prefrontal cortex (F3) and medial prefrontal cortex (Fpz). The CBT was provided individually based on the exposure technique at 12–20 sessions, twice a week. All clinical measures were assessed at baseline, after the intervention, and at 3-month follow-up. Results SAD symptoms significantly decreased after intervention and follow-up in all groups, with no significant differences between them. However, CBT + tDCS resulted in a numerically larger symptom reduction, significantly exceeding CBT + sham tDCS on the fear scale. Depressive states and trait worry significantly improved in all groups post-intervention and at the 3-month follow-up, with no between-group differences. Quality of life (total scores, physical, and psychological domains) significantly improved after the and at the 3-month follow-up only in the CBT + tDCS and tDCS-alone groups with no between-group differences. Conclusion Psychotherapeutic interventions​ with CBT, intensified tDCS targeting the prefrontal cortex, and the combined CBT-tDCS are effective for alleviating primary and secondary clinical symptoms in individuals with SAD. The combined CBT-tDCS intervention showed superior efficacy in reducing the primary symptoms of SAD. Trial registration ID IRCT20220421054607N1, registration date: 19/05/2022, available at: https://irct.behdasht.gov.ir/trial/63119 .